The Design and Application of Online Exam System Supported by Database - Sakir TASDEMIR; Mehmet BALCI; Ayse CABI; Mustafa ALTIN; Osman CABI (International Journal of Applied Methods in Electronics and Computers, 2015)
The fast developments in the computer technology and the internet becoming common in every part of our lives especially in recent years have become indispensable in the teaching and learning field of students and instructors. Web-based studies have brought innovations also in the education field and in this field, various applications have become common. This study covers the technical and functional features of the online exam system carried out and being used in Selcuk University Higher School of Vocational and Technical Sciences. The automation was set up on a database system and the administrator, academician and students can access the system over the web server. The software which is dynamical structure and application simplicity working on the web server (in the web environment) can be applied on the exams of the students who take different courses in the higher school. The Online Exam System (OES) that was created enables instructors to make question banks with the choices of using shapes, multiple choice and multiple answers and to evaluate the applied exams instantaneously. OES, instant evaluation of examinations and gives students the opportunity to watch the performance. Via OES, positive contributions are provided for both the instructors and the students in terms of particularly place and time in the education field.